Molecular Epidemiology Questions Transmission Pathways Identified During the Year 2000 Outbreak of Classical Swine Fever in the UK - Strong, Rebecca; McCleary, Stephen; Grierson, Sylvia; Choudhury, Bhudipa; Steinbach, Falko; Crooke, Helen R. (Frontiers in Microbiology, 2022)
The last outbreak of classical swine fever (CSF) in the UK occurred in 2000. A total of 16 domestic pig holdings in the East Anglia region were confirmed as infected over a 3-month period. Obtaining viral genome sequences has since become easier and more cost effective and has accordingly been applied to trace viral transmission events for a variety of viruses. To examine if genetic changes over the course of any future CSF outbreak would allow to track virus movements, the E2 gene and full genome of virus present in archived tonsil samples from 14 of these infected premises were sequenced. Insufficient changes occurred in the full E2 gene to discriminate between the viruses from the different premises. However, phylogenetic analysis of full CSFV genome sequences allowed to either corroborate or question some of the transmission pathways inferred by epidemiological investigations at the time. We are thus confident that in future outbreaks real time monitoring of the outbreak via full genome sequencing will be beneficial. For sequence data to provide the most useful information to aid disease control efforts genetic diversity needs to occur to distinguish between closely related viruses. The rate of genetic evolution varies for different viruses and is influenced by different transmission events, which will vary according to the epidemiology of an outbreak. Our data provides information on the extent of virus change between infected premises in the absence of virus replication in a wildlife reservoir. Further knowledge on the extent of virus evolution under different situations, such as mutations per passage and by different infection routes, is important to assist in interpreting the significance of genetic changes.